1991
DOI: 10.1037/0096-3445.120.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Depressive deficits in memory: Focusing attention improves subsequent recall.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(166 citation statements)
references
References 29 publications
(49 reference statements)
10
155
0
Order By: Relevance
“…We replicated the recall deficit found by Ellis et al when we used their method and eliminated it when we used our own. Later, we extended our findings to clinically depressed outpatients, nondepressed outpatients, and outpatients recovered from depressive episodes (Hertel & Rude, 1991a). The mean percentages of words recalled from the more distinctive frames are shown in Fig.…”
Section: On Tests Of Free Recallmentioning
confidence: 94%
“…We replicated the recall deficit found by Ellis et al when we used their method and eliminated it when we used our own. Later, we extended our findings to clinically depressed outpatients, nondepressed outpatients, and outpatients recovered from depressive episodes (Hertel & Rude, 1991a). The mean percentages of words recalled from the more distinctive frames are shown in Fig.…”
Section: On Tests Of Free Recallmentioning
confidence: 94%
“…In the more constrained condition, performance of the two groups did not differ. Hertel and Rude (1991) concluded that people with depression did not perform poorly because resources were not available, but because of a deficit in the initiative to allocate resources to the task. This raises the question of whether the above considerations imply that days with varying levels of negative affect are days with reduced performance in WM.…”
Section: Variability In Working Memory and Negative Affectmentioning
confidence: 99%
“…Within-person relations will also be called couplings in the following. Our interest was inspired by quasi-experimental studies showing a relationship between these variables; in particular, studies on performance deficits in people with depressive symptoms that point to the role of attentional and motivational deficits (e.g., Ellis & Ashbrook, 1988;Hertel & Rude, 1991), and experimental studies manipulating emotions that show reliable effects on cognitive performance (e.g., Ellis, Moore, Varner, Ottaway, & Becker, 1997;Richards & Gross, 2000). Critical questions that emerged when applying this background to the question of correlates of day-to-day variability of WM within individuals were (a) whether more subtle day-today fluctuations of, for example, negative affect are meaningful enough to impact on performance, especially in comparison to between-person differences in depressive symptoms; and (b) whether more generally, the mechanisms that are discussed as underlying relationships between variables operate similarly at the between-and the within-person level of analysis.…”
mentioning
confidence: 99%
“…The evidence described above regarding the elimination of depressive deficits in recall by requiring attention to the target words during incidental learning (Hertel & Rude, 1991a) is one example of such an attempt. Instructions to image during initial exposure to materials is yet another way.…”
Section: Specific Procedures For Memory Improvementmentioning
confidence: 99%
“…In the incidental learning phase of an experiment by Hertel and Rude (1991a), outpatients exhibiting symptoms of unipolar depression, recovered outpatients, and nonpsychiatric controls judged the semantic fit of words into easy or difficult sentence frames. One learning condition was similar to the procedure of Ellis et al (1984, Experiment 3): The word and the frame were displayed concomitantly, and subjects judged the fit whenever they chose to do so during the duration of the trial.…”
Section: Depressive Deficitsmentioning
confidence: 99%